IMPLEMENTASI MANAJEMEN PEMBELAJARAN TAHFIZ ALQURAN DI SMP ISLAM TERPADU AL KHOLIS SIDODADI SIDOMULYO LAMPUNG SELATAN - Dewi Rukmini; Sulthan Syahril; Yuli Habibatul Imamah (UNISAN JURNAL, 2024)
The exploration points are educators who remember the Al-Qur'an, school chiefs, managerial staff, and class IX understudies. One of the exploration did is subjective examination. Information assortment was helped out through meetings, perception and archive study. Then every one of the gathered information was examined in two phases. From this exploration, the accompanying things are made sense of: 1) The Koran remembrance educational plan isn't executed in that frame of mind of an educational program or GBPP. So the Koran remembrance educational program subjects at Al Kholis Sidodadi Coordinated Islamic Center not entirely settled by the school head for each level and semester, which are called courses. 2) In getting the hang of arranging, the managing educator doesn't make a showing arrangement, yet rather gives data by let understudies know which letters should be retained toward the start of the semester. 3) Educating to retain the Al-Qur'an is done in specific classes, while direction on perusing the Al-Qur'an (Further developing perusing) is remembered for class hours. 4) The strategy for remembering the Qur'an has not been broadly grown, so the two techniques, to be specific monotheism and tuning in, are generally utilized. 5) The job of the overseeing educator impacts understudies in figuring out how to retain the Al-Qur'an. 6) Instructive evaluation is done on every understudy's memory stores with the regulating educator, and toward the finish of every semester. The parts assessed comprise of: a. Retain it with great, b. Right perusing as per pitch and manner of speaking) c. Peruse cautiously